Externalizing and Internalizing Behaviors in Children with ADHD during Lockdown for COVID-19: The Role of Parental Emotions, Parenting Strategies, and Breaking Lockdown Rules - Maria Grazia Melegari; Pietro Muratori; Oliviero Bruni; Enrica Donolato; Martina Giallonardo; Irene Mammarella (MDPI AG, 2022)
Lockdown experience for COVID-19 pandemic significantly affected children and adolescents with Attention-Deficit/Hyperactivity Disorder (ADHD) exacerbating or promoting the onset of externalizing and internalizing symptoms. However, few studies have considered how externalizing and internalizing behaviors changed in relation to parental emotions and parenting strategies. In the present study, 992 caregivers of children and adolescents with ADHD from 5 to 18 years were presented with an online survey evaluating youths' externalizing and internalizing behaviors, their non-compliance with lockdown rules, and parental factors related to parental emotions and parenting strategies. Two hierarchical linear regression models were performed to examine the contribution of children's non-compliance with lockdown rules, parental emotions, and parenting strategies on children's externalizing and internalizing behaviors. Results revealed that externalizing behaviors were higher in children and adolescents with ADHD non-compliant with lockdown rules. Moreover, positive parenting strategies moderated the relationship between non-compliance with lockdown rules and externalizing behaviors. Differently, higher internalizing behaviors were observed in children with ADHD who had parents reporting more negative emotions and positive parenting strategies. In this case, parents' negative emotions had a moderator effect in the association between internalizing behaviors and non-compliance to lockdown measures. The clinical implications of these two different patterns of relations are discussed.